The Relationship of Anemia In Pregnant Women With Low Birth Weight - Suparni, Ita Eko; Dina Mariana, Bety (Journal of Applied Nursing and Health, 2024)
Background: Pregnancy anemia is one indicator of measuring the success of a nation's health development. Anemia in pregnant women can increase the risk of LBW. As adults, LBW babies have a greater risk of stunting. This study aimed to determine the relationship between the incidence of anemia in pregnant women and low birth weight in the Ngancar Community Health Center area, Kediri Regency. Methods: This research design uses a retrospective cohort. The population in this study was 346 respondents, and the sample was 186. A simple random sampling technique and measuring instruments were used in the form of a Pregnancy Mother's Register Book and a Childbirth Register Book. The research was conducted on 20-25 August 2023 in the Ngancar Community Health Center Working Area, Kediri Regency. The independent variable is the incidence of anemia in pregnant women (X), and the dependent variable is low birth weight (LBW) (Y). Bivariate data analysis with Spearman Rank with a significant value (p ˂ 0.05). Results: The results of data analysis using Spearman Rank regarding the relationship between the incidence of anemia in pregnant women and Low Birth Weight obtained a significant value (p) of 0.0001 (p < 0.05). Thus, it is stated that there is a relationship between the incidence of anemia in pregnant women and low birth weight. Conclusion: Anemia can increase the occurrence of LBW, but from this research, it is known that not all pregnant women with anemia in their pregnancies will give birth to LBW babies because anemia is not the only factor causing LBW. Pregnancy checks are done monthly, and good nutrition and Fe tablets are needed to prevent anemia and LBW